Analisis Perbandingan Ekstrak Kulit Buah Naga (Hylocereus polyrhizus) dan Kunyit (Curcuma longa L.) Sebagai Indikator Identifikasi Boraks Pada Makanan - Claudia Nainggolan; Eka Setiawan; Emon Sejahtera Zendrato; Grecia Trinatal Simbolon; Kania Restya Diva; Larasati Arum Utami; Rejeki Sihite (Jurnal Biogenerasi, 2026)
This study aimed to analyze and compare the effectiveness of red dragon fruit peel (Hylocereus polyrhizus) extract and turmeric (Curcuma longa L.) extract as natural indicators for detecting borax in food samples. The research used a laboratory experimental method with a qualitative descriptive approach. Food samples tested included sausages, ketupat, lontong, white tofu, crackers, siomay, meatballs, cilok, pempek, nuggets, white noodles, and yellow noodles. The testing process was conducted by dripping dragon fruit peel extract and turmeric extract onto each sample and observing the resulting color changes. The results showed that most samples tested negative for borax, while meatballs and yellow noodles indicated positive results. The color change in turmeric to reddish-brown occurred due to the reaction between curcumin and borax, while dragon fruit peel extract changed color because anthocyanin pigments are sensitive to pH changes. The findings indicate that both natural materials can be used as simple, inexpensive, safe, and effective natural indicators for the qualitative preliminary detection of borax in food. However, further quantitative testing is needed to obtain more accurate results.